Design and Control of Hybrid Electric Light Rail Vehicles With Open Ended Winding Machines - Davide De Simone; Maria Stefania Carmeli; Salvatore D'Arco; Luigi Piegari; Pietro Tricoli (IEEE Open Journal of Vehicular Technology)
Light railways are a low carbon emission form of transport, but it is often difficult to electrify tracks in central urban areas. This limitation can be avoided by integrating an on-board battery storage connected to the dc bus of the traction inverter with a boost dc/dc converter. However, the boost converter requires a bulky inductor and introduces additional power losses that are undesirable. This paper proposes to replace the standard induction motor with an open ended winding induction motor connected at one end to the overhead line with the traction inverter and to the other end to a battery with a second inverter in order to reduce the power losses of the traction drive. The paper addresses design and control aspects for light rail vehicles with open ended winding induction machines when the power supply is partly from the overhead line and partly from the on board battery. Moreover, the paper studies in detail the hybrid operations of the traction system i.e., when the overhead line charges the battery during coasting or at the stops. Finally, numerical simulations for a real use case are presented to quantify the reduction of power losses in comparison to the standard solution.